β-cyclodextrin Mediated Green Synthesis of Bioactive Heterocycles - Tayade, Yogesh A.; Wagh, Yogesh Baburav; Dalal, Dipak Sharadrao (Current Organic Chemistry, 2023)
In this review, we report β-cyclodextrin catalyzed green transformations of biologically active heterocycles. β-Cyclodextrin is a seminatural product, water-soluble, highly efficient, and biodegradable catalyst. β-Cyclodextrin is a versatile catalyst and promotes a variety of multicomponent transformations, biomimetic reactions, C-C bond formation, and synthesis of some biologically active natural products. It has been applicable to attain some name reactions, deprotection of THP/MOM/Ac/Ts ethers, oxidative cleavage of epoxides, oxidative dehydrogenation of alcohol, regioselective cyclization of chalcone epoxides and 2'-aminochalcones. The catalyst is useful to carry out diastereoselective reactions, and it also plays a very important role in phase transfer catalysts.
Keywords: heterocycles